Recombinant dermatan sulfate is a potent activator of heparin cofactor II-dependent inhibition of thrombin - Tykesson, Emil (Glycobiology, 2019)
The glycosaminoglycan dermatan sulfate (DS) is a well-known activator of heparin cofactor II-dependent inactivation of thrombin. In contrast to heparin, dermatan sulfate has never been prepared recombinantly from material of non-animal origin. Here we report on the enzymatic synthesis of structurally well-defined DS with high anticoagulant activity. Using a microbial K4 polysaccharide and the recombinant enzymes DS-epimerase 1, dermatan 4-O-sulfotransferase 1, uronyl 2-O-sulfotransferase and N-acetylgalactosamine 4-sulfate 6-O-sulfotransferase, several new glycostructures have been prepared, such as a homogenously sulfated IdoA-GalNAc-4S polymer and its 2-O-, 6-O- and 2,6-O-sulfated derivatives. Importantly, the recombinant highly 2,4-O-sulfated DS inhibits thrombin via heparin cofactor II, approximately 20 times better than heparin, enabling manipulation of vascular and extravascular coagulation. The potential of this method can be extended to preparation of specific structures that are of importance for binding and activation of cytokines, and control of inflammation and metastasis, involving extravasation and migration.